Hydrogen sulphide: a versatile tool for the regulation of growth and defence responses in horticultural crops - Fotopoulos, Vasileios; Christou, Anastasis; Manganaris, George A.; Antoniou, Chrystalla (My University, 2015)
The improvement of plant growth and productivity under biotic and abiotic stress conditions, as well as the reduction of post-harvest losses, are of paramount significance for meeting the increasing global population demand for food. Hydrogen sulphide (H2S) has recently appeared as a key contributor towards this goal via its bioactive role in the regulation of plant defence responses. Here, we provide an up-to-date overview of recent literature concerning the biosynthesis and regulation of H2S within the plant cell, as well as its involvement in a series of plant physiological processes. More precisely, H2S is actively associated with growth and developmental processes, tolerance responses following exposure to stress factors in horticultural plants, as well as in post-harvest fruit physiology. The H2S-mediated enhancement of tolerance following exposure of plants to several abiotic stress factors is highlighted, with particular emphasis on the priming effects of H2S on anti-oxidant capacity, redox regulation, and signalling, as well as transcriptional regulation of cellular defence components. Moreover, H2S has been reported to be associated with seed germination, increased growth and organogenesis in roots, while at the same time it enhances post-harvest performance and anti-oxidant capacity of fruit. The present review proposes a role for H2S in the physiology of horticultural crops, further supporting the hypothesis that H2S acts as a key signal molecule in plants, possibly involved in cross-talk with other secondary messengers in plants.
Keywords: Hydrogen sulphide; Horticultural crops; Versatile tool